RELIGIOUS PLURALISM ACCORDING TO THE THOUGHT OF NURCHOLISH MADJID IN THE INDONESIAN CONTEXT - Ahmad Faqihuddin (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
Pluralism cannot be separated from the meaning of plurality, if plurality is a difference in religious, ethnic, cultural or other issues, while pluralism is a system of values, attitudes and processes that can translate religious reality into sustainable social cohesion. In other words, diversity is something empirical, while pluralism is an ideology or understanding that accepts diversity as a positive value accompanied by efforts to negotiate and adjust among them, without trying to weaken or even destroy one or part of that diversity. The existence of a difference in religion is a reality in society, and a pluralist attitude is an orientation that assumes acceptance and sincere relationship to that fact, rather than eliminating or destroying or melting the differences into one.This type of research is library research (Libary research) The results of this study collected that: According to Nurcholish Madjid, the noble values of Indonesianness are universal and cosmopolitan values of the Indonesian nation based on religion or culture as a result of a long dialogue with religion, these values have a strategic role as well as a central role in building the unity of the people to foster self-esteem as a nation. The issue of the relationship between religion, citizens and the nation is a matter of ijtihad that is closely related to the socio-political contacts understood by the people themselves.